Diagnostic value of the combined test of leukocytes in urine and TB-DOT and T-SPOT.TB in blood for urinary tuberculosis - Li, Yanyan; Wang, Yachun; Wei, Lukuan; Wang, Wei (Frontiers in Microbiology, 2025)
BackgroundThis study aims to evaluate the clinical utility of routine urinary tests and renal function assessments, as well as the Tuberculosis antibody test (TB-DOT) and T-cell spot tests for TB infection (T-SPOT.TB), either individually or in combination, for diagnosing urinary tuberculosis (UTB).MethodsWe conducted a retrospective analysis of urinary routine tests, renal function tests, TB-DOT, and T-SPOT.TB—administered alone or in combination—in 95 patients suspected of having UTB from January 2020 to December 2022 at our institution.ResultsSignificant differences were observed in the levels or positivity of white blood cells (WBC), red blood cells (RBC), creatinine (Crea), TB-DOT, and T-SPOT.TB between the UTB group and the non-UTB group (P < 0.05). Among the individual tests, T-SPOT.TB exhibited the highest specificity and positive predictive value (PPV), while WBC demonstrated the highest area under the curve (AUC). Both TB-DOT and RBC showed relatively good sensitivity. Additionally, WBC levels correlated with both TB-DOT and T-SPOT.TB results. The combination of WBC, TB-DOT, and T-SPOT.TB provided the best sensitivity, negative predictive value (NPV), and AUC when evaluated in parallel with the other tests.ConclusionFor the early identification of UTB, the sensitivity of T-SPOT.TB and TB-DOT tests is superior to that of routine urinary and renal function tests. The parallel combination of WBC, TB-DOT, and T-SPOT.TB offers enhanced diagnostic efficacy for UTB, facilitating rapid clinical diagnosis.